Tác động của uy tín người ảnh hưởng đến ý định mua lặp lại: Vai trò của mối quan hệ xã hội một chiều và bài đăng kể chuyện - Nguyễn Trần Bá, Ngữ; Nguyễn Thị Mai, Trang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This study examines the influence of social media influencers’ credibility on followers’ repurchase intention by focusing on the mediating role of parasocial relationships and the moderating role of storytelling posts in the influencer marketing context. Data was collected from 300 social media users who had a shopping experience after viewing the content posted by the influencer. The results showed that (1) the influencer’s credibility (expertise, trustworthiness, attractiveness) has a positive impact on the parasocial relationship, then (2) the parasocial relationship has a positive effect on repurchase intention, (3) and this relationship is moderated by storytelling post.